Between the concession and the adversity: Clauses introduced by aunque in Spanish under functionalist approach - Garcia, Talita Storti [UNESP]; Felipe, Mariana Alves Machado Pelegrini [UNESP] (Universidade Estadual de Maringa, 2019)
This work investigates the sentences of the spoken Spanish introduced by aunque, connector that, according to the grammatical compendiums, can indicate a concessive or adversative relation in Spanish language. From the perspective of the functional discourse grammar theory (Hengeveld & Mackenzie, 2008), we intend to investigate how the phenomenon of semantic overlap between concession and adversity is conceived and, in a specific way, to investigate in which levels and layers of the model this overlap occurs. The results show that the dubious cases postulated by the traditional perspective occur in the interpersonal domain, when they constitute rhetorical functions and interactional functions.
Entre a concessão e a adversidade: Orações introduzidas por aunque no espanhol sob o viés funcionalista
Keywords: Adversity; Aunque; Concession; Functional discourse grammar; Spoken peninsular Spanish